2010
DOI: 10.1002/pssb.200945575
|View full text |Cite
|
Sign up to set email alerts
|

Displacive phase transition, structural stability, and mechanical properties of the ultra‐incompressible and hard MoN by first principles

Abstract: The structural stability, electronic, and mechanical properties of MoN were investigated by use of the density functional theory. Nine structures were considered, i.e., hexagonal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…d-MoN is known to crystallize at least in three crystal structures: d-MoN with a WC structure type (space group P% 6m2), 18 d-MoN with a NiAs structure type (space group P6 3 /mmc), and d-MoN with a distorted NiAs structure (space group P6 3 mc). [18][19][20] The structure of Mo 5 N 6 in P6 3 /m crystallizes in the MoS 2 -type structure. 21 For the refinement of all data containing hexagonal d-MoN, crystal structures in space groups P% 6m2 and P6 3 mc were considered.…”
Section: Introductionmentioning
confidence: 99%
“…d-MoN is known to crystallize at least in three crystal structures: d-MoN with a WC structure type (space group P% 6m2), 18 d-MoN with a NiAs structure type (space group P6 3 /mmc), and d-MoN with a distorted NiAs structure (space group P6 3 mc). [18][19][20] The structure of Mo 5 N 6 in P6 3 /m crystallizes in the MoS 2 -type structure. 21 For the refinement of all data containing hexagonal d-MoN, crystal structures in space groups P% 6m2 and P6 3 mc were considered.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is not only the first face‐sharing arrangement of FeN 6 octahedra in a nitride, but also the single NiAs‐type 3d transition‐metal nitride. Although some have been predicted, such as VN and MoN, they remain elusive and only heavier homologues, such as δ‐NbN and TaN, have been successfully synthesized. Comparison of the interatomic iron distances of NiAs‐type FeN and ϵ ‐iron with the same iron arrangement reveals that d (Fe–Fe) along the c axis varies only slightly (2.467 Å versus 2.442 Å) whereas along the a axis there is a larger difference: In the nitride, the Fe–Fe distance is significantly larger than in ϵ ‐iron (2.737 Å versus 2.473 Å).…”
Section: Figurementioning
confidence: 99%
“…Kanoun et al [38] and more recently Zhao et al [39] have also calculated the bulk modulus corresponding to the stoichiometric MoN phase of hexagonal structure by use of the density functional theory ( Table 3). The analysis of the density of states of δ1-MoN and δ3-MoN phases show that the high values of bulk modulus result from the covalent character of the bonding due to the strong hybridization between N and Mo states [38].…”
Section: Stoichiometric δ-Mon and Cubic Mon Phasesmentioning
confidence: 99%
“…Zhao et al [39] have reported that among the hexagonal structures, δ2-MoN has the largest bulk modulus, which is equal to 356 GPa. This value can be compared with the one of c-BN equal to 370 GPa.…”
Section: Stoichiometric δ-Mon and Cubic Mon Phasesmentioning
confidence: 99%